Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.04.15.043257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vibrio Cholerae Adapts to Sessile and Motile Lifestyles by Cyclic Di-GMP Regulation of Cell Shape

Abstract: The cell morphology of rod-shaped bacteria is determined by the rigid net of peptidoglycan forming the cell wall. While V. cholerae grows into a curved shape under most conditions, straight rods have been observed. However, the signals and regulatory pathways controlling cell shape transitions in V. cholerae and the benefits of switching between rod and curved shape have not been determined. We demonstrate that cell shape in V. cholerae is regulated by the bacterial second messenger cyclic dimeric guanosine mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 49 publications
(2 reference statements)
0
17
0
Order By: Relevance
“…The spiral nature of V. cholerae filaments (Fig. 1D) is due to the natural curvature of V. cholerae mediated by crvA [33,34].Taken together, these results indicated that DcdV overexpression severely impacts cell physiology in the absence of VSP-1.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…The spiral nature of V. cholerae filaments (Fig. 1D) is due to the natural curvature of V. cholerae mediated by crvA [33,34].Taken together, these results indicated that DcdV overexpression severely impacts cell physiology in the absence of VSP-1.…”
mentioning
confidence: 73%
“…Cells were imaged as previously described [34]. Briefly, overnight cultures were diluted 1:1000 into LB supplemented with antibiotics and IPTG.…”
Section: Fluorescence Microscopy and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Vibrio cholerae, the pathogen responsible for the diarrheal disease cholera, typically adopts a characteristic comma (curved) shape. In PNAS, Fernandez et al (2) report that cellular curvature in V. cholerae is regulated by the second messenger cyclic dimeric guanosine monophosphate (c-di-GMP), whose levels are known to regulate cell motility (3) and biofilm formation (4). Fernandez et al further suggest that c-di-GMP regulation of cell shape may provide an advantage during environmental transitions in which motility and formation of a sessile biofilm are alternately beneficial (4).…”
mentioning
confidence: 99%